James Joyce, Ulysses, and the construction of Jewish identity : culture, biography, and "the Jew" in modernist Europe - Davison, Neil R. (Cambridge University Press, 1996)
Representations of 'the Jew' have long been a topic of interest in Joyce studies. Neil Davison argues that Joyce's lifelong encounter with pseudo-scientific, religious and political discourse about 'the Jew' forms a unifying component of his career. Davison offers new biographical material, and presents a detailed reading of Ulysses showing how Joyce draws on Christian folklore, Dreyfus Affair propaganda, Sinn Fein politics, and theories of Jewish sexual perversion and financial conspiracy. Throughout, Joyce confronts the controversy of 'race', the psychology of internalised stereotype, and the contradictions of fin-de-siècle anti-Semitism.